Isolated frogs in a crowded world: Effects of human-caused habitat loss on frog heterozygosity and fluctuating asymmetry. (March 2016) - Eterovick, Paula C.; Sloss, Brian L.; Scalzo, José A.M.; Alford, Ross A.
Abstract: It is important to develop research methods that will detect deterioration in population health before severe declines occur. Amphibian population declines are widespread; the main causes are anthropogenic and include habitat fragmentation due to agriculture, mining, fires, and urban development. Brazil is the richest country in species of amphibians, and the Brazilian regions with the greatest amphibian diversity are experiencing relatively high rates of habitat destruction. We tested the use of measurements of fluctuating asymmetry (FA) taken on adult frogs, as well as heterozygosity estimates in frog populations, to detect anthropogenic stress. We hypothesized that greater human occupancy in the landscape might result in more stressful conditions for amphibians, which would be reflected in high FA levels and/or reduced heterozygosity. We conducted this study at the Espinhaço mountain range in southeastern Brazil, using an endemic species ( Bokermannohyla saxicola, Hylidae) as a model. We found that adult frog FA levels differed among localities but did not find significant correlations between human modification of the landscape and FA levels. In the subsample of localities for which we had genetic data, heterozygosity was significantly inversely correlated with FA in adult frogs, and heterozygosity decreased with increasing human occupancy in the landscape, except for populations with marginal distribution within the species range that already had very low heterozygosity. Our major finding was that reduced heterozygosity may be caused by population isolation resulting from human occupancy (among other causes) and is correlated with increased fluctuating asymmetry, so that either may indicate higher levels of stress in populations of B. saxicola . Highlights: We test predictive tools to indicate anthropogenic stress on frog populations. Frog fluctuating asymmetry is not related to human occupancy in the landscape. Human occupancy in the landscape reduces heterozygosity of frog populations. Reduced frog population heterozygosity leads to increased fluctuating asymmetry. Human occupancy in the landscape is likely to disrupt frog migration routes.